Transcriptomic Analysis for Differentially Expressed Genes in Ovarian Follicle Activation in the Zebrafish - Zhu, Bo; Pardeshi, Lakhansing; Chen, Yingying; Ge, Wei (Frontiers in Endocrinology, 2018)
In teleosts, the onset of puberty in females is marked by the appearance of the first wave of pre-vitellogenic (PV) follicles from the pool of primary growth (PG) follicles (follicle activation) in the ovary during sexual maturation. To understand the mechanisms underlying follicle activation and therefore puberty onset, we undertook this transcriptomic study to investigate gene expression profiles in the event. Our analysis revealed a total of 2,027 up-regulated and 859 down-regulated genes during the PG-PV transition. Gene Ontology (GO) analysis showed that in addition to basic cellular functions such as gene transcription, cell differentiation, and cell migration, many up-regulated genes were enriched in such biological processes as steroidogenesis, cell signaling and angiogenesis; by comparison, some processes were down-regulated including piRNA metabolism, gene silencing and proteolysis. Further Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis identified a variety of signaling pathways that might play pivotal roles in PG-PV transition, including MAPK, TGF- Hedgehog, FoxO, VEGF, Jak-STAT, and phosphatidylinositol signaling pathways. Other pathways of particular interest included endocytosis and glycosaminoglycan biosynthesis. We also analyzed expression changes of genes expressed in different compartments viz. oocytes and follicle cells. Interestingly, most oocyte-specific genes remained unchanged in expression during follicle activation whereas a great number of genes specifically expressed in the follicle cells showed significant changes in expression. Overall, this study reported a comprehensive analysis for genes, biological processes and pathways involved in follicle activation, which also marks female puberty onset in the zebrafish when occurring for the first time in sexual maturation.